If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -1) + 8(x * 3) = 6x + 7 + -5x Reorder the terms: -3(-1 + x) + 8(x * 3) = 6x + 7 + -5x (-1 * -3 + x * -3) + 8(x * 3) = 6x + 7 + -5x (3 + -3x) + 8(x * 3) = 6x + 7 + -5x Reorder the terms for easier multiplication: 3 + -3x + 8(3x) = 6x + 7 + -5x Remove parenthesis around (3x) 3 + -3x + 8 * 3x = 6x + 7 + -5x Multiply 8 * 3 3 + -3x + 24x = 6x + 7 + -5x Combine like terms: -3x + 24x = 21x 3 + 21x = 6x + 7 + -5x Reorder the terms: 3 + 21x = 7 + 6x + -5x Combine like terms: 6x + -5x = 1x 3 + 21x = 7 + 1x Solving 3 + 21x = 7 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 21x + -1x = 7 + 1x + -1x Combine like terms: 21x + -1x = 20x 3 + 20x = 7 + 1x + -1x Combine like terms: 1x + -1x = 0 3 + 20x = 7 + 0 3 + 20x = 7 Add '-3' to each side of the equation. 3 + -3 + 20x = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 20x = 7 + -3 20x = 7 + -3 Combine like terms: 7 + -3 = 4 20x = 4 Divide each side by '20'. x = 0.2 Simplifying x = 0.2
| 12.6+4m=9.8+8m | | 2(m-1)=3(2-m) | | ln(10-x)=2ln(x+2) | | 10(x+5)=20x | | 64*n=364 | | n=16+m | | r-93=-38 | | 4.5+a=1 | | 11a-12=45 | | -3(-7k-6)=2k+18 | | 8(x-3)=16x | | 6+9x=12+3x | | b-2=49 | | 6a-8(a+2)=-5a-25 | | 7=j+87 | | -4-2a=-2(8+2a)-2a | | w+40=89 | | 5x-35=3x+15 | | 8(1+3x)=27+5x | | (3x-4)(4x-3)=(6x-4)(2x-4) | | u-32=62 | | X^2+12x=54 | | 7(10-X)-(4-X)=48 | | 12(x-5)=-22x | | x-8=3x+1 | | ln((6y/7z)) | | 46=2.5+z | | -(x+1)=-26+4x | | .4x+2=-1.1x+4 | | 10(x+4)=18x | | 4x+4y=970 | | x=90-0.5x |